Candida albicans Promotes Oral Cancer via IL-17A/IL-17RA-Macrophage Axis - Wang, Xu; Wu, Shuangshaung; Wu, Wenjie; Zhang, Wenqing; Li, Linman; Liu, Qian; Yan, Zhimin (mBio, 2023)
The relationship between fungi and cancer is gradually receiving attention. Among them, some clinical evidence has shown that Candida may be a contributor to gastrointestinal cancers, especially oral cancer. The association between Candida albicans ( C. albicans ) and oral cancer (OC) has been noticed for a long time, but the mechanisms for C. albicans promoting OC are rarely explored. In this study, we determined that C. albicans infection promoted OC incidence in a 4-nitroquinoline 1-oxide (4NQO)-induced mouse tongue carcinogenesis model as well as promoted OC progression in a tongue tumor-bearing mouse model (C3H/HeN-SCC VII). We then demonstrated that tumor-associated macrophage (TAMs) infiltration was elevated during C. albicans infection. Meanwhile, the attracted TAMs polarized into M2-like macrophages with high expression of programmed death ligand 1 (PD-L1) and galectin-9 (GAL-9). Further analysis suggested that the interleukin (IL)-17A/IL-17RA pathway activated in OC cells was a contributor to the excessive TAMs infiltration in C. albicans -infected mice. Thus, we constructed IL-17A neutralization and macrophage depletion experiments in C3H/HeN-SCC VII mice to explore the role of IL-17A/IL-17RA and TAMs in OC development caused by C. albicans infection. The results showed that both IL-17A neutralization and macrophage depletion tended to reduce the TAMs number and tumor size in mice with C. albicans infection. Collectively, our finding revealed that C. albicans promoted OC development via the IL-17A/IL-17RA-macrophage axis, opening perspectives for revealing C. albicans -tumor immune microenvironment links. IMPORTANCE The relationship between fungi and cancer is gradually receiving attention. Among them, some clinical evidence has shown that Candida may be a contributor to gastrointestinal cancers, especially oral cancer. However, the underlying mechanisms for Candida promoting oral cancer need to be explored. For this reason, this study demonstrated the role of C. albicans in oral cancer development. Moreover, this study revealed the underlying mechanisms for C. albicans promoting oral cancer from the perspective of the tumor immune microenvironment.